Determination of Lamivudine and Zidovudine from Human Plasma by High Performance Liquid Chromatography-UV Detection for Bioequivalence Studies - R. MORE, ABHIJIT; VAIDYA, A.J.; VAIDYA, V.V.; DESHMUKH, R.G. (Asian Journal of Chemistry, 2010)
A HPLC- method with UV detection at wavelength of 270 nm is described for the determination of lamivudine and zidovudine in human plasma using fluconazole as internal standard. Lamivudine and zidovudine were isolated by solid phase extraction using methanol as the solvent. Selection of mobile phase components was a critical factor in achieving good chromatographic peak shape and resolution. Good separation of the target compounds and short run time were obtained using an elution system of buffer:methanol:acetonitrile (85:10:5 % v/v). UV wavelength of 270 nm also provided better sensitivity. This assay achieved higher sensitivity and better specificity for the analysis of lamivudine and zidovudine in human plasma. The limit of quantification of ng/mL for lamivudine and zidovudine was thus attainable by HPLC-UV. The internal standard proved to be good internal standard for this assay. No significant interference caused by endogenous compounds was observed. This simple and rapid assay can be successfully used in pharmacokinetic studies of lamivudine and zidovudine.